1989
DOI: 10.1007/bf00197452
|View full text |Cite
|
Sign up to set email alerts
|

Human tumor necrosis factor increases the resistance against Listeria infection in mice

Abstract: The resistance in mice against Listeria infection was augmented by treatment with recombinant human tumor necrosis factor (TNF). To elucidate this phenomenon, we examined the effect of TNF on macrophage activation. TNF-treated macrophages had listericidal activity in vitro and superoxide anion production. In addition, macrophage migration was inhibited in the presence of TNF. Therefore, activation of macrophages by TNF was similar to activation by macrophage-activating factor or macrophage-migration-inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
1
25
0
2
Order By: Relevance
“…Through the activation of nuclear factor kappa B (NF-rB), a key transcriptional factor for immunological system, TNF-a facilitates the protection from invading pathogens [2]. By utilizing neutralizing anti-TNF-a antibodies, studies have demonstrated that host defense against exogenous pathogens is severely compromised in the absence of TNFa [3][4][5]. However, dys-regulated TNF-a has been implicated as a host-attacking mediator in a variety of human diseases, including autoimmune diseases, inflammatory bowel disease (IBD) and osteoporosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Through the activation of nuclear factor kappa B (NF-rB), a key transcriptional factor for immunological system, TNF-a facilitates the protection from invading pathogens [2]. By utilizing neutralizing anti-TNF-a antibodies, studies have demonstrated that host defense against exogenous pathogens is severely compromised in the absence of TNFa [3][4][5]. However, dys-regulated TNF-a has been implicated as a host-attacking mediator in a variety of human diseases, including autoimmune diseases, inflammatory bowel disease (IBD) and osteoporosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…TNF is produced shortly following infection with L. monocytogenes, and neutralization of TNF with specific antibodies exacerbates listeriosis in mice (16,17,27). Administration of recombinant human TNF can also reduce the severity of primary infection with L. monocytogenes in mice (20,33). The importance of this cytokine-receptor pair during the primary immune response to L. monocytogenes was confirmed when TNF Ϫ/Ϫ (28) and TNFRI Ϫ/Ϫ (9, 30, 34) mice were found to be highly susceptible to primary listeriosis.…”
mentioning
confidence: 99%
“…Since IL-12 [33,34] or TNF-α [35] have been shown to reduce bacilli burdens during bacterial infection, We evaluated if statin treatment also enhanced IL-12p40 and TNF- α production in BMDMs. Macrophages were treated with simvastatin and stimulated with IFN-γ for 18 hours and subsequently infected with L.…”
Section: Resultsmentioning
confidence: 99%